Cerium and Gadolinium co-doped perovskite oxide for a protonic ceramic fuel cell cathode. (22nd October 2019) - Zhang, Limin; Yang, Shuyan; Zhang, Shizhen; Yang, Yongxing
Abstract: Proton-conducting ceramic fuel cells (PCFCs) show unique advantages over oxygen-ionic-conducting counterparts at intermediate and low temperatures, which have attracted significant attention worldwide in recent years. A critical issue for world-spread applications is inadequate performance due to the lack of appropriate cathodes for PCFCs. Here, cubic perovskite BaCo0.4 Fe0.5-x Ce0.1 Rex O3-δ (ReY, Gd x = 0, 0.1) materials are successfully synthesized and evaluated as the cathode in the PCFCs based on BaCe0.7 Zr0.1 Y0.1 Yb0.1 O3-δ as an electrolyte material. The Y- or Gd-doped perovskite BaCo0.4 Fe0.4 Ce0.1 Y0.1 O3-δ (BCFCeY), BaCo0.4 Fe0.4 Ce0.1 Gd0.1 O3-δ (BCFCeG) exhibit larger lattice parameters, and higher electrocatalytic activity comparing to their parent oxide BaCo0.4 Fe0.5 Ce0.1 O3-δ (BCFCe). Among them, BCFCeG shows the best performance. The single cell with BCFCeG as the cathode material exhibits an interfacial polarization resistance as low as 0.12 Ω cm 2 and delivers a promising peak power density of 504 mW cm −2 at 600 °C, while the BCFCe-based cell achieves only 437 mW cm −2 at 600 °C. The X-ray diffraction (XRD) results show good chemical compatibility for BCFCeG below 1050 °C. Moreover, it shows favorable stability in CO2 -containing environment. This work confirms that BCFCeG could be a promising cathode for PCFCs. Highlights: Y- or Gd-doped BaCo0.4 Fe0.5 Ce0.1 O3-δ were evaluated as cathodes for PCFCs. Y or Gd doping enhanced the electrocatalytic activity. The cell with BCFCeG showed the maximal power density of 504 mW cm −2 at 600 °C. BCFCeG cathode is promising for PCFCs.